Facelift surgery and nerve injury: a systematic review and meta-analysis. - Bia Santos Silva (2022)
Background: Advances on surgical procedures resulted in aesthetic surgery's better safety profile. Several side effects have been described for facelift surgeries, and nerve injuries constitute one of the most dreaded, due to its impact on quality of life. The main goal of this work is the evaluation of the rate and type of nerve injuries during facelift procedures, through a systematic review of the literature Methods: PubMed®, EMBASE® and Web of Science® databases were searched for articles on nerve injury rates after facelift surgeries according to PRISMA guidelines, using controlled and non-controlled terms for establishing search queries. Two investigators assessed publications for eligibility independently, first based on title and abstract, and afterwards based on full text. DerSimonian-Laird random-effects model was used for proportion estimation through a meta analysis. Results: A total of 67 eligible publications with a total of 15 404 patients and 15 441 procedures were included analysis based on eligibility criteria. Overall estimated pooled motor and sensory nerve damage rate were 0.66% (95% confidence interval [95%CI]: [0.5% ; 0.9%], Z = 6.07, p < .001) and 0.39% (95%CI: [0.2% ; 0.6%], Z = 4.16, p < .001), respectively. For permanent neuronal damage, estimated pooled rates were 0.047% (95%CI: ]0.0% ; 0.1%], Z = 2.69, p = .007) and 0.045% (95%CI: ]0.0% ; 0.1%], Z = 2.63, p = .009), respectively for motor and sensory nerve damage. Conclusions: There is increasing awareness for nerve-damage as a serious complication of facelift surgery, although its estimated pooled rates are lower than 1%.